2012
DOI: 10.1161/strokeaha.112.656587
|View full text |Cite
|
Sign up to set email alerts
|

No Increased Risk of Symptomatic Intracerebral Hemorrhage After Thrombolysis in Patients With European Cooperative Acute Stroke Study (ECASS) Exclusion Criteria

Abstract: Background and Purpose-The European Cooperative Acute Stroke Study (ECASS) III trial used additional exclusion criteria not present in current guidelines for thrombolytic therapy in the United States (age Ͼ80 years; National Institutes of Health Stroke Scale Ͼ25, combination of previous stroke and diabetes, aggressive measures required to control blood pressure [intravenous infusion], and oral anticoagulant treatment). We tested the hypothesis that thrombolysis is not safe in patients with 1 of the additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…Symptomatic hemorrhage was 5.7% compared with 6.8% in the <3-hour group (P=0.49); ambulation at discharge was noted in 26.6% versus 24.7% (P=0.53); and discharge home occurred in 30.5% versus 26.4% (P=0.38). 377 In a smaller study by Cronin et al, 376 2 of 11 patients (18.2%) on warfarin had sICH compared with 3.9% of those not taking warfarin (P=0.09), but mortality was similar between groups (P=0.49).…”
Section: Warfarin Usementioning
confidence: 94%
See 2 more Smart Citations
“…Symptomatic hemorrhage was 5.7% compared with 6.8% in the <3-hour group (P=0.49); ambulation at discharge was noted in 26.6% versus 24.7% (P=0.53); and discharge home occurred in 30.5% versus 26.4% (P=0.38). 377 In a smaller study by Cronin et al, 376 2 of 11 patients (18.2%) on warfarin had sICH compared with 3.9% of those not taking warfarin (P=0.09), but mortality was similar between groups (P=0.49).…”
Section: Warfarin Usementioning
confidence: 94%
“…Not surprisingly, however, in-hospital mortality was higher among those >80 years of age (16.1% versus 3.8%; P=0.02). 376 In a study that examined the impact of removing specific exclusions for intravenous alteplase in stroke, if the upper age limit were removed for treatment in the 3-to 4.5-hour window, the percentage of eligible patients would increase from 26% to 29%.…”
Section: February 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15] There are also now randomized trial data from the Third International Stroke Trial (IST-3), which enrolled patients for whom there was equipoise regarding the benefits of thrombolytic therapy and randomized to treatment with IV tPA versus placebo ≤6 hours from onset. 16 This study included 1617 patients aged >80 years and found that although the rate of good outcome in that group was overall lower than younger patients, there was still a significant benefit to treatment with IV tPA.…”
Section: September 2014mentioning
confidence: 99%
“…However, the presence of single exclusion criterion, such as age >80 years, baseline NIHSS scores >25, or combination of prior stroke and diabetes mellitus, is not necessarily associated with an increased risk of SICH. 15 Hopefully, applying risk score models to identify low-risk patients might increase the number of patients with stroke who could benefit from intravenous thrombolytic therapy.…”
Section: June 2013mentioning
confidence: 99%